PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR DI ACEH BARAT - Arief Aulia Rahman; Luthfiana Mirati (Universitas Sarjanawiyata Tamansiswa, 2019)
This research aims to determine the influence realistic Mathematics Education approach on motivation and learning achievements of elementary school students in West Aceh. This research uses a quantitative approach, it is a quasi-experimental type research and the population fifth grade elementary school students in West Aceh. The research samples were selected using a simple random sampling. The data collection was conducted by means of questionnaires and tests. The collected data were tested using a MANOVA test. Based on the data analysis results, it was shown that: there is a significant influence from realistic Mathematics Education approach on motivation and learning achievements of fifth grade elementary school students in West Aceh. The proof showed that 35 fifth grade students from Peureumee State Elementary School who were respondents in this research had an average of 80.57 for learning motivation and an average of 70.74 for learning achievements. Whereas students from Peunaga Cut Ujong State Elementary School who were in the control group had an average of 69.15 for learning motivation and an average of 60.24 for learning achievements. This shows that the motivation and learning achievement between students who were given RME approach are higher than those who were given conventional teaching. And the analysis results on F value for Pillae Trace, Wilk Lambda, Hotelling Trace, and Royâ€™s Largest Rootx showed a significance of 0.000, or lower than 0.05. This means that the F values were all significant. They indicate that â€œthere is a significant influence from realistic Mathematics Education approach on motivation and learning achievements of fifth grade elementary school students.â€ Furthermore, a test on determinant coefficient showed that RMEâ€™s influence on motivation was 60.2%, and on learning achievements was 20.1%, and the rest was influenced by other variables not included in the study.